Pengaruh Kecerdasan Emosional (EQ), Kecerdasan Spiritual (SQ), Perilaku Belajar Dan Metode Mengajar Dosen Terhadap Tingkat Pemahaman Akuntansi Mahasiswa Prodi Akuntansi Universitas Islam Majapahit - Fauziah Nur Aini; Hari Setiono; Tatas Ridho Nugroho (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to examine the effect of emotional intelligence, spiritual intelligence, learning behavior and teaching methods of lecturers on the level of understanding of student accounting. This research was conducted on undergraduate students of the Accounting Study Program, Faculty of Economics, Islamic University of Majapahit. This type of research is associative quantitative research. The population used in this study were all accounting study program students, totaling 104 respondents. The sample used was 77 respondents with purposive sampling technique. Data collection techniques using a questionnaire, with a Likert scale as a measuring tool. Data analysis in this study was linear regression analysis with the help of SmartPLS version 3.0 software. The results of this study indicate that emotional intelligence has no significant positive effect on the level of understanding of accounting, spiritual intelligence has a significant positive effect on the level of understanding of accounting, learning behavior has a significant positive effect on the level of understanding of accounting. accounting, lecturer teaching methods have no significant positive effect on the level of understanding of accounting.